THE PHENOMENA OF TEACHING CAAD AND MULTIMEDIA IN ARCHITECTURE EDUCATION AT PETRA CHRISTIAN UNIVERSITY - Danny Santoso Mintorogo (DIMENSI (Journal of Architecture and Built Environment), 2001)
The department of architecture at Petra Christian University has offered CAAD and Multimedia for almost ten years, with particular emphasis on the architectural design studios and the final design studio process. As the beginner of CAD users, students with different of CAD skills-right after taking the fundamental of architectural CAD and Multimedia-tend to explore and use CAD in many different ways, such as very few students are using CAD as a design tool, and the others as a production tool mainly. Multimedia has long been firmly conceived, as a great interactive-presentation tool, as an automation within the digital domain of conventional hand-worked animation techniques of presentations. For being the students of 7th and 8th (final) architectural design studios, the crucial issues of creative exploration within a design, simulation, and visualization techniques are of greater importance than those of media-blue prints production information only.